Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s40608-016-0136-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality and marketing strategies of fast food children’s combo meals in Guatemala

Abstract: BackgroundOverweight and obesity prevalence in children is now on the rise in low/middle-income countries, including Guatemala. Fast food consumption is a recognized contributing factor to this rise. Fast food restaurants use health claims, toy giveaways, price incentives and fast service to promote children’s combo meals. This study sought to assess the use of toy giveaways, time to delivery and price incentives as marketing strategies in fast food chain restaurants in Guatemala. In addition, we sought to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 20 publications
1
47
0
1
Order By: Relevance
“…Twenty-five studies inquired several topics related with television advertisement. Fourteen of them found that food and nonalcoholic beverage advertisements represented between 5.6% and 36.4% of all television ads 24,[27][28][29]34,36,37,40,43,49,52,53,56,59 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies inquired several topics related with television advertisement. Fourteen of them found that food and nonalcoholic beverage advertisements represented between 5.6% and 36.4% of all television ads 24,[27][28][29]34,36,37,40,43,49,52,53,56,59 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite a decrease in spending on toys/premiums to promote children's meals in fast‐food restaurants in the United States (Federal Trade Commission, ), studies have consistently found that price promotions and toys are used in other countries as a way to market children's meals in fast‐food restaurants (e.g., Guatemala: Mazariegos, Chacón, Cole, & Barnoya, ).…”
Section: Study 1: Observations Of Food and Beverage Promotion In Retamentioning
confidence: 99%
“…An analysis of six fast food chain restaurants in Guatemala, five international (McDonald's, Burger King, Wendy's, Kentucky Fried Chicken, and Pizza Hut) and one local (Pollo Campero), found that they all have children's combo meals, ranging from five (McDonald's) to two different combos per chain (Pizza Hut). 36 Even though taxation is promising strategy to decrease fast food consumption, 37 this might not be the case in Guatemala. Children´s combo meals have been found to be expensive, ranging from a median of 3.77 (Pizza Hut) to 3.50 dollars (Kentucky Fried Chicken).…”
Section: Food Marketing and The Obesity Epidemicmentioning
confidence: 99%
“…Children´s combo meals have been found to be expensive, ranging from a median of 3.77 (Pizza Hut) to 3.50 dollars (Kentucky Fried Chicken). 36 This accounts for nearly a third of the daily minimum wage in Guatemala (11 dollars). Regardless, on average, children's combo meals are 1.93 dollars less expensive than purchasing children's meal items individually (p= 0.01), and most meals also included a toy giveaway.…”
Section: Food Marketing and The Obesity Epidemicmentioning
confidence: 99%
See 1 more Smart Citation